A remote-controlled IoT solution for environmental automation in broiler poultry housing: Enhancing welfare under unstable power conditions - Abdi, Satriadi Bin; Patiran, Abdul Zaid; Rehiara, Adelhard (Social, Ecology, Economy for Sustainable Development Goals Journal, 2025)
Background: Broiler chickens are highly sensitive to temperature changes due to their inability to sweat, making them vulnerable to heat stress and respiratory illnesses. Manual monitoring methods are inadequate in maintaining optimal environmental conditions, especially in regions with unstable power supply. This study addresses the need for an autonomous system to regulate temperature and lighting in poultry housing. Methods: An IoT-based solution was developed using Arduino Uno and NodeMCU ESP8266 microcontrollers, coupled with a DHT11 temperature and humidity sensor. The system employed incandescent lamps for heating and axial fans for cooling, activated based on temperature thresholds. Real-time data were displayed on an LCD and transmitted to the Blynk mobile application for remote access. A 12V battery and inverter ensured continuous operation during power outages. Findings: The system maintained stable temperature conditions between 31°C and 34°C. When the temperature dropped below 31°C, the lamp activated; when it rose above 34°C, the fan turned on. Data were reliably recorded and displayed over a 24-hour period. All hardware components functioned effectively, and system performance was consistent even during transitions to backup power. Conclusion: This research confirms the effectiveness of a low-cost IoT-based system for automated environmental control in broiler poultry housing. The system provides a reliable, remote-controlled solution that improves animal welfare, minimizes manual labor, and ensures operational resilience in power-limited settings. Novelty: The proposed system combines real-time environmental monitoring, remote access, and automated actuation with a backup power feature in a compact and affordable design. It is specifically tailored for small-scale poultry operations in developing regions, filling a critical gap in accessible precision farming tools.